Evaluating the Geotechnical and Geophysical Characteristics of Expanding Districts in Tehran Using Field Experiments - Arash Razmyar; Abolfazl Eslami (Civil Engineering Journal, 2018)
Considering the increasing population growth and the rapid growth of urbanization and pollution in the environment, providing zoning maps and urban engineering geology seem to be important. The rapid construction growth of cities, as well as the confrontation with events such as earthquakes and failure to observe the geological and geotechnical issues, has caused many engineering problems. The use of geophysical methods not only cannot lonely provide us a complete and comprehensive information on the geotechnical conditions of the earth but also has many disturbances in urban areas, and its use in urban centers is almost impractical. Therefore, it seems that the best way of examining and interpreting the geotechnical characteristics of a site, especially in urban areas, is the use of suspicious data. Therefore, performing geotechnical studies and geotechnical zoning can be useful for retrofitting buildings and engineering structures and reducing their risks. Hence, zoning studies are conducted in this research in order to better recognize the technical soil status for safe construction due to rising the population of Tehran in recent decades and the concentration of population in certain areas of Tehran, especially in the eastern and western regions (districts 4 and 22). In this study, different geotechnical field tests such as standard penetration test (SPT), cone penetration test (CPT) were used to estimate parameters such as adhesion coefficient (C), internal friction angle ( ), Young modulus (E). Other common experiments with conventional geophysical experiments, such as in good experiments, refractive and CSSW were applied to estimate geophysical parameters of bedrock depth and shear wave velocity for zoning these areas.